The Spectrophotometric Determination of Famotidine Drug via Coupling with Diazotized Metochlopramide Hydrochloride - Baghdad Science Journal (مجلة بغداد للعلوم)
A new, simple and sensitive spectrophotometric method was described for the determination of famotidine (FAM) as a pure material and in pharmaceutical formulation. This method was based on diazotization and coupling reaction between famotidine and diazotized solution of metochlopramide hydrochloride (DMPH) in the presence of phosphate buffer solution to give a compound of azo dye having orange color soluble in water with high absorptivity at a wave length of 478 nm. The data shows that FAM and DMPH combine in the molar ratio of 1:1 at PH 7.0 .The method obeys Beer's law over concentration range of 1-40 ?g.ml-1 of famotidine with a correlation coefficient of 0.9955 and a detection limit of 0.10 ?g.ml-1. The apparent molar absorptivity referred to famotidine has been found to be 2.0 x 104 L. mol-1cm. -1. The proposed method was applied successfully to the assay of famotidine in pharmaceutical preparation.